Early Gut Microbiota Changes in Preterm Infants with Bronchopulmonary Dysplasia: A Pilot Case–Control Study - Chen, Shan-Ming; Lin, Ching-Pin; Jan, Ming-Shiou (American Journal of Perinatology, 2020)
Objective Bronchopulmonary dysplasia (BPD) is a complex chronic lung disease that primarily affects premature or critically ill infants. This pilot study investigated early changes in gut microbiota composition in BPD patients and explored the potential risk factors associated with these changes.Study Design Preterm infants admitted to our neonatal intensive care unit with a gestational age of 26 to 32 weeks were prospectively surveyed and eligible for stool collection on days 7 and 28 of postnatal age between February 2016 and June 2017. A 16S rRNA sequencing approach was applied to compare the gut microbiota composition between the BPD group and controls. Multiple linear regression analysis was used to identify the predictor variables.Results Eight subjects in the BPD group and 10 subjects in the preterm group were analyzed during the observation period. Actinobacteria, Proteobacteria, Bacteroidetes, and Firmicutes were the four dominant bacteria phyla of intestinal microflora. A significantly lower diversity of gut microbiota was observed in the BPD group compared with the preterm group on day 28 (number of observed operational taxonomic units, p = 0.034; abundance-based coverage estimator, p = 0.022; Shannon index, p = 0.028). Multiple linear regression analysis revealed that high Neonatal Therapeutic Intervention Scoring System score (≧19) at 24 hours was statistically significant in predicting the proportion of aerobic with facultative anaerobic bacteria on day 28 (p = 0.002).Conclusion Infants with BPD are prone to develop gut dysbiosis in early life. A higher severity of illness and treatment intensity may indicate a higher risk of disrupting an anaerobic environment in the gut during the first month of life.Key Points
Keywords: bronchopulmonary dysplasia; dysbiosis; gut microbiota; next-generation sequencing; neonatal intensive care unit